MODEL PEMBELAJARAN LITERASI QUR’ANI ONE DAY ONE PAGE DI SEKOLAH AL-QUR’AN WAHDAH ISLAMIYAH BOGOR - Samsuddin; Abdul Jabar Idharudin; Ali Maulida; Indri Machtifaliandri (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to describe and analyze the Qur’anic literacy learning model implemented through the One Day One Page (ODOP) program at Sekolah Al-Qur’an Wahdah Islamiyah Bogor. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving the dormitory head, dormitory supervisors, and students as research participants. Data were analyzed through data reduction, data display, and conclusion drawing, while source and method triangulation were applied to ensure data trustworthiness. The findings reveal that the ODOP program represents an integrated Qur’anic literacy learning model that combines qira’ahh (reading), tafhim (comprehension), tadabbur (reflection), and kitabah (writing) within a systematic and sustainable learning cycle. The implementation of the model is supported by daily reading habits, teacher guidance, Majelis Tadabbur (weekly reflection forums), and reflective evaluation processes. The model not only enhances students’ ability to read and understand the Qur’an but also contributes to the development of reading interest, reflective thinking skills, discipline, responsibility, and spiritual awareness. This study proposes an Integrated Qur’anic Literacy Model Based on Qira’ahh–Tafhim–Tadabbur–Kitabah, which conceptualizes Qur’anic literacy as a holistic learning process that integrates cognitive, affective, social, and spiritual dimensions in fostering students’ literacy culture.